2022
DOI: 10.3389/fmed.2022.804847
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of XEN Gel Stent Implantation: A Systematic Review and Meta-Analysis

Abstract: PurposeXEN gel stents are used for the treatment of open-angle glaucoma (OAG), including primary and secondary glaucoma that are uncontrolled by previous medical therapy and cases with previous failed surgery. Our aim was to systematically review of the clinical data of currently published ab-interno XEN gel stents with an emphasis on intraocular pressure (IOP), antiglaucoma medication outcomes, and safety profiles.MethodsWe analyzed all of the publications (MEDLINE, EMBASE, Cochrane Library) on the ab-interno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 97 publications
4
39
4
2
Order By: Relevance
“…A systematic review of XEN stent and cataract surgery revealed an average reduction of 1.86 drops with a range of 1.4 to 3.1. 35 In addition, a meta-analysis of iStent implants revealed an average medication reduction of 1.2 for a follow-up time between 36 and 60 months. 36 Our study demonstrated an average number of glaucoma medication reduction of 1.2, with XEN being significantly different than the other two stent groups with a reduction of 2.8 number of medications compared to 0.4 in the iStent group and the Hydrus group ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review of XEN stent and cataract surgery revealed an average reduction of 1.86 drops with a range of 1.4 to 3.1. 35 In addition, a meta-analysis of iStent implants revealed an average medication reduction of 1.2 for a follow-up time between 36 and 60 months. 36 Our study demonstrated an average number of glaucoma medication reduction of 1.2, with XEN being significantly different than the other two stent groups with a reduction of 2.8 number of medications compared to 0.4 in the iStent group and the Hydrus group ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…34 Lastly, a systematic review of XEN gel stent found an overall IOP reduction of 35% across their meta-analysis. 35 We Mean (SD) − found that patients who underwent either of the three stent implantations had an average of 2.2 mmHg drop in IOP, or a 12.9% decrease, within 12 to 18 months. Notably, with a baseline IOP of 17.1 mmHg and a final average number of glaucoma drops of 1.5, it is unsurprising there was a modest IOP reduction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, literature reports mean IOP reductions of >20% by 12 months, generally ranging from 25-47% in XEN stents implanted both with and without concurrent phacoemulsification. 1,[11][12][13][14]…”
Section: Discussionmentioning
confidence: 99%
“…However, retrospective studies of patients receiving MicroShunt implants who specifically had prior failed subconjunctival glaucoma surgery reported higher rates of choroidal effusion development, ranging from 9.6 to 12.9% [24,25], suggesting that a more complex ocular history may increase the risks of postoperative complications such as choroidal effusions, even with minimally invasive approaches. Several recent studies have also reported on the incidence of choroidal effusions in patients receiving the XEN45 gel stent, with ranges between 1.3 and 19.8% depending on the technique used [26,27,28 ▪ ,29,30].…”
Section: Risk Factors For Choroidal Effusion Developmentmentioning
confidence: 99%